Formulasi dan Evaluasi Mikroemulsi Antikerut Ekstrak Beras Hitam (Oryza sativa L.) - Ardian Baitariza; Sasanti Tarini Darijanto; Jessie Sofia Pamudjie; Irda Fidrianny; Shelvi E. Suherman (Indonesian Journal of Pharmaceutical Science and Technology, 2014)
Free radicals in the body can lead to wrinkle. The use of antioxidants can prevent wrinkle. Black rice known to have an antioxidant effect. The purpose of this study is to get a microemulsion preparation of black rice extract that stable and has antiwrinkle effect. Research was started by antioxidant power test in vitro against DPPH, then the optimization of the microemulsion preparation base. The optimum base formula then formulated with black rice extract. Then tested the chemical and physical stability test, also antiwrinkle effect. The results showed that black rice extract microemulsion has composition as black rice extract of 4%, VCO of 28.8%, Croduret-50-SS of 28.8%, glycerol of 28.8%, and citrate phosphate buffer pH 3.0 of 9.6%. The antiwrinkle effectivity of black rice extract in microemulsion form was more than in emulsion form. The average decrease of wrinkle level by black rice extract microemulsion was 44.46%±19.7%, and by black rice extract emulsion was 36.6%±19.5%.       Keywords: Antiwrinkle, black rice, microemulsion